Predicting mother and child emotional availability in Singaporean bilingual English and Mandarin dyads : a multilevel approach to the specificity principle - Esposito, Gianluca (2021)
When interacting with one another, bilingual caregivers and their young bilingual children can switch from one language to another to convey emotion and information in meaningful ways. The Specificity Principle (Bornstein, 2017) states that specific setting conditions affect specific outcomes in specific ways in specific individuals at specific times. Here we tested three constituents of the Specificity Principle: We evaluated how the language used in interaction (setting condition) differentially affects different dimensions of emotional availability (outcomes) in mothers and children (individuals). Twenty-six Singaporean English-Mandarin bilingual mother-child dyads (Mother M age = 33 years; Child M age = 19 months) participated in two counterbalanced play sessions, one exclusively in English and one exclusively in Mandarin. Using recursive-partitioning analyses, we assessed (i) how child language dominance, dimensions of maternal emotional availability, and mother-child physiological synchrony accounted for dimensions of child emotional availability and (ii) how child language dominance, child emotional availability, and mother-child physiological synchrony accounted for overall maternal emotional availability. In agreement with predictions from the Specificity Principle, our results show that different predictors of different dimensions of child and mother emotional availability differ according to whether the mother interacted with her child in the child's dominant or non-dominant language. The findings suggest that language specificity influences the quality of mother-child interactions.